Robakidze's Works written in the German Language : Prometheus' Offspring - Nugesha Gagnidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
The society has been interested in Grigol Robakidze's works written in German for a long time. Due to the fact that the writer's new works were tracked down in various countries, new prospects are open for scholars and literary critics for studying his literary heritage. Robakidze's five articles, under the umbrella title The Silhouette of the Caucasus - published in 1942 in different issues of The Brussels Magazine, are not known to Georgian readers. The above articles are mentioned by the writer in his letter My Explanation addressed to Georgian writers in 1947. As Robakidze notes, he managed to avoid "political emphasis" during the fierce years of World Was II.